Does Population Sorting through Internal Migration Increase Healthcare Costs and Needs in Peripheral Regions? - Shobhit Kulshreshtha; Martin Salm; Ansgar Wübker (Institute of Labor Economics (IZA), 2022)
Large regional disparities in health and healthcare costs prevail in many countries, but our understanding of the underlying causes is still limited. This study shows for the case of the Netherlands that population sorting through internal migration can explain a substantial share, around 28%, of regional variation in healthcare costs. Internal migration during the 1998-2018 period increases average healthcare costs in peripheral provinces by up to 3%. Most of this effect can be attributed to selective migration. We find similar results for risk scores, a measure of healthcare needs. The Dutch risk equalization scheme compensates only partially for these effects.
Keywords: H51; I14; R23; 330; regional variation in healthcare costs; internal migration; movers approach; regional disparities